Independence corrupted: how America's judges make their decisions - Schudson, Charles Benjamin (The University of Wisconsin Press, 2018)
Part One. Judges. Who's the judge? -- Where judges are born: the prosecutor's perspective - from battered homes to nursing homes -- The decision-making ideal -- Part Two. In chambers: how America's judges really make their decisions -- The trial judge: birth, aborted : State v. Monica Migliorino Miller -- The appellate judge: birth, premature : Peterman v. Midwestern National Insurance Company, Special Products, Inc., Frank A. Busalacchi, and Visuals Plus, Inc. -- Standard of review: humility, and the division of labor -- The trial judge: life, and a lost teenager : In the interest of S.W., a child under eighteen years of age -- The appellate judge: life, and a sex predator : State v. Shawn Schulpius -- The trial judge: death, and a cherished child : State v. Anthony McClain -- The appellate judge: death, and three widows : Wischer v. Mitsubishi Heavy Industries of America, Inc. -- The trial judge: religion, and white supremacists : State v. Hollin Lange and Patrick O'Malley -- The appellate judge: politics, "on the point" : State v. L.C. Clay -- Indigestion (and other determinants) -- Part Three. America's judiciary in the new age of vanishing independence -- Judicial campaigns: declarations and contributions -- Begging the question: elective or appointive